Basement membrane collagen type IV expression by human mesenchymal stem cells during adipogenic differentiation - Sillat, Tarvo (Blackwell Publishing Ltd, 2012)
During adipogenic differentiation human mesenchymal stem cells (hMSC) produce collagen type IV. In immunofluorescence staining differentiating hMSCs started to express collagen type IV when Oil Red O-positive fat droplets appeared intracellularly. Quantitative real time-polymerase chain reaction confirmed progressive increase of collagen type IV α1 and α2 mRNA levels over time, 18.6- and 12.2-fold by day 28, respectively, whereas the copy numbers of α3–α6 mRNAs remained rather stable and low. Type IV collagen was in confocal laser scanning microscopy seen around adipocytes, where also laminins and nidogen were found, suggesting pericellular deposition of all key components of the fully developed basement membrane. Immunofluorescence staining of matrix metalloproteinase-2 (MMP-2, 72 kD type IV collagenase, gelatinase A) and MMP-9 (92 kD type IV collagenase, gelatinase B) disclosed only faint staining of MSCs, but MMP-9 was strongly induced during adipogenesis, whereas MSC supernatants disclosed in zymography pro-MMP-2 and faint pro-MMP-9 bands, which increased over time, with partial conversion of pro-MMP-2 to its active 62 kD form. Differentiation was associated with increasing membrane type 1-MMP/MMP-14 and tissue inhibitor of metalloproteinase-2 (TIMP-2) staining, which may enable participation of type IV collagenases in basement membrane remodelling via ternary MT1-MMP/TIMP-2/MMP-2 or −9 complexes, focalizing the fully active enzyme to the cell surface. MMP-9, which increased more in immunofluorescence staining, was perhaps preferentially bound to cell surface and/or remodelling adipocyte basement membrane. These results suggest that upon MSC-adipocyte differentiation collagen type IV synthesis and remodelling become necessary when intracellular accumulation of fat necessitates a dynamically supporting and instructive, partly denatured adipogenic pericellular type IV collagen scaffold.